1987
DOI: 10.3109/02713688709025183
|View full text |Cite
|
Sign up to set email alerts
|

The effects of forskolin on cyclic AMP, intraocular pressure and aqueous humor formation in rabbits

Abstract: Forskolin was used to study cyclic AMP-mediated regulation of aqueous humor dynamics in rabbits. Crystalline forskolin was solubilized in oil and its pharmacological effects were studied both in vitro and following topical ocular administration. In vitro, using cultured corneal epithelial cells, forskolin rapidly stimulated cyclic AMP production and in vivo increased cyclic AMP concentration in the aqueous humor 10-fold following topical administration. The effect of topical forskolin on intraocular pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The authors also recorded no changes in blood pressure and pulse during and after topical ocular delivery of forskolin in rabbits and humans, and observed no tolerance to the intraocular pressure lowering effect in rabbits after topical doses given every 6 h for 15 days. In addition, forskolin was found to stimulate cAMP production in rabbit cultured corneal epithelial cells, increase cAMP concentration in the aqueous humor 10fold and cause a prolonged reduction of intraocular pressure and a decrease in aqueous humor formation [115]. It has however been shown that topical application of 1% forskolin did not significantly decrease the intraocular pressure in glaucomatous monkey eyes after the second day of the treatment [116].…”
Section: Forskolinmentioning
confidence: 99%
“…The authors also recorded no changes in blood pressure and pulse during and after topical ocular delivery of forskolin in rabbits and humans, and observed no tolerance to the intraocular pressure lowering effect in rabbits after topical doses given every 6 h for 15 days. In addition, forskolin was found to stimulate cAMP production in rabbit cultured corneal epithelial cells, increase cAMP concentration in the aqueous humor 10fold and cause a prolonged reduction of intraocular pressure and a decrease in aqueous humor formation [115]. It has however been shown that topical application of 1% forskolin did not significantly decrease the intraocular pressure in glaucomatous monkey eyes after the second day of the treatment [116].…”
Section: Forskolinmentioning
confidence: 99%
“…Nakano et al, 1992). Numerous studies have found that stimulation of adenyl cyclase (Gregory et al, 1981;Burstein et al, 1984;Lee et al, 1984;Mittag & Tormay, 1985Nilsson et al, 1986;Bartels et al, 1987;Mittag et al, 1987Mittag et al, , 1993a or inhibition of cAMP phosphodiesterase (Mishima et al, 1991;Mittag et al, 1993a) in the ciliary epithelium lowers intraocular pressure. Conversely, inhibition of adenyl cyclase has been shown to decrease cAMP levels in the ciliary epithelium (Tobin & Osborne, 1989) and increase intraocular pressure (Meyer-Bothling et al, 1993).…”
Section: Aqueous Productionmentioning
confidence: 99%
“…Since intraocular pressure (IOP) is a function of the balance between fluid input and drainage out of the globe, the strategies for the treatment of open-angle glaucoma fall into two classes: reduction of aqueous humor secretion and enhancement of aqueous outflow (1)(2)(3)(4)(5)(6)(7)(8). Cholinomimetics, aagonists and b-blockers have been found to be useful in reducing IOP, and the clinical application of these agents has been well established in patients with glaucoma (1)(2)(3)(4)(5)(6)(7)(8). However, little is known about the signal transduction underlying postreceptor adrenergic and cholinergic processes in a discrete portion in the eye, partly due to the lack of a versatile yet sensitive assay of adenylate cyclase activity for the minute tissue mass (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%